2007
DOI: 10.1051/0004-6361:20066920
|View full text |Cite
|
Sign up to set email alerts
|

Exact expression of the impact broadening operator for hydrogen Stark broadening

Abstract: Aims. Recent measurements on the Stark broadening of radio recombination lines show values and trends in disagreement with conventional theories. Different attemps to explain those disagreements have not been successfull for any of the employed theoretical models. In particular, the impact model that describes well the physical conditions at which the studied broadenings occur, shows a functional trend upon the principal quantum number of the studied transitions that does not correspond to the experimental obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 22 publications
1
29
1
Order By: Relevance
“…Figure 5 shows the FWHM of the He I 7281 line as a function of the electron density for the studied temperatures. For this spectral line it can be observed that the relation between the FWHM and N has a functional dependence on the exponent g(N e , T ) that is practically independent of the density and temperature and very close to the value g ≈ 1, as expected from spectra whose width is caused basically by electron impact (Griem 1974;Gigosos et al 2007).…”
Section: Calculation Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Figure 5 shows the FWHM of the He I 7281 line as a function of the electron density for the studied temperatures. For this spectral line it can be observed that the relation between the FWHM and N has a functional dependence on the exponent g(N e , T ) that is practically independent of the density and temperature and very close to the value g ≈ 1, as expected from spectra whose width is caused basically by electron impact (Griem 1974;Gigosos et al 2007).…”
Section: Calculation Resultssupporting
confidence: 70%
“…Naturally, the characteristic time of the dynamic of the electronic fields is much lower than the loss the correlation time of the emitter dipole at very low densities, when the typical Stark effect is very weak and the lines are narrow. Under these circumstances, the considerations of the impact model are very convenient (Gigosos et al 2007) and the simulations perfectly reproduce that situation: the width and the shift of the lines are linear with the electron density and fit to the so-called impact limit.…”
Section: Comparison With Other Resultsmentioning
confidence: 91%
“…More than thirty years ago, a discussion took place about the physical meaning of the so-called interference term [26,27,28,29,30]. That term does not account for any physical requirement: it results from a mathematical expansion in power series.…”
Section: The Collision Operator 21 General Formmentioning
confidence: 99%
“…Poquérusse & Alexiou (2006) have extended standard semi-classical impact theory for hydrogen-like ions to include penetrating collisions. For transitions in highly excited hydrogen-like atoms and ions Stambulchik & Maron (2008) have produced a simple analytical method for calculating line shapes and Gigosos et al (2007) have developed an exact expression for the impact broadening operator of hydrogen. The asymmetry of hydrogen lines has been studied by Demura et al (2008a) and Demura et al (2008b).…”
Section: Stark Broadeningmentioning
confidence: 99%